Bulk δ15N measurements of organic‐rich rock samples by elemental analyzer/isotope ratio mass spectrometry with enhanced oxidation ability. (28th November 2016) - Han, Wennian; Feng, Lianjun; Li, Hongwei; Liu, Wei
Abstract : Rationale: Elemental analyzer/isotope ratio mass spectrometry (EA/IRMS) has been widely used for nitrogen isotope ratio determination in various organic and inorganic samples. However, the extent of the redox reaction in the EA reaction tube can greatly affect the accuracy and precision of measurements, especially in the case of complex geological samples. It is therefore necessary to determine the appropriate reaction conditions to reach a high recovery of nitrogen by complete combustion or thermal decomposition and quantitative reduction. Methods: The conventional Dumas dual‐inlet method was used to determine the bulk nitrogen isotope composition of SGR‐1 (an organic‐rich standard sample), which then was analyzed by EA/IRMS under different EA reaction conditions to study the influence of the redox environment on the δ 15 N measurements. The measured data together with the results reported by previous researchers were used to evaluate the effectiveness of the nitrogen extraction for organic‐rich rock samples. Results: Our results demonstrated that with the Dumas dual‐inlet method more oxidizing agent (CuO) addition to SGR‐1 would yield a higher nitrogen content of 0.91% than the recommended content (0.81%) although a δ 15 N value of 17.39 ± 0.09‰ was consistent with the recommended value by USGS. Using EA/IRMS, when more O2 was injected in the reaction tube, a high nitrogen content (0.92 ± 0.01%) and a δ 15 N value (17.43 ± 0.17‰) close to that of the Dumas dual‐inlet method were obtained. The addition of V2 O5 or CuO in a continuous‐flow system of EA/IRMS could not effectively enable the complete combustion of SGR‐1. Conclusions: When measuring the nitrogen isotope composition of organic‐rich rock sample dominated by reduced substances with EA/IRMS, greater O2 injection will enable more complete combustion to obtain reliable nitrogen yields compared with the addition of V2 O5 or CuO. Copyright © 2016 John Wiley & Sons, Ltd.